THE INFLUENCE OF EMOTIONAL INTELLIGENCE AND SELF-EFFICACY ON ORGANIZATIONAL CULTURE AND ITS IMPACT ON TEACHER PERFORMANCE IN PUBLIC SENIOR HIGH SCHOOLS IN PESANGGRAHAN AND KEBAYORAN DISTRICTS - Yusdarti, Marlia; Noviandy Aulia, Irfan (Dinasti Publisher, 2020)
The purpose of this research is to know and analyze the influence of emotional intelligence and self-efficacy on organizational culture and its impact on teachers performance. The research method in this study is a quantitative method that used type of expansive research. The population in this study was honorer teachers or KKI of 7 Public Senior High Schools in Pesanggrahan and Kebayoran Lama sub-districts totaly 54 people. The sample determination method in the study uses non-probability sampling with sample determination using the entire population. The data analysis method used in this study is Multiple Linear Regression using the help of statistical product for service solution (SPSS) program version 25. Previously, instrument validity testing was conducted using Pearson Product Moment Correlation and reliability test was conducted. The results showed that emotional intellegence and self-efficacy had a positive and significant effect on the organization's culture and teacher performance.